PEMANFAATAN MEDIA PEMBELAJARAN INTERAKTIF KAHOOT PADA PEMBELAJARAN MATEMATIKA KELAS V SDN DUNGKEK I - Umma Fathimah Sabilah Faradis; Titin Wahyuni; Raudiyatus Zakiyah Romadhani; Hilaliyatul Fithriyah; Feri Aprillah; Matroni Matroni; Tutuk Nuryati (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This study aims to describe the use of the interactive learning media Kahoot in increasing student engagement in mathematics learning in grade V at SDN Dungkek 1. This study uses a qualitative descriptive method with data collection techniques through observation, documentation, and literature study. The results show that the use of Kahoot can make the learning process more interesting and enjoyable so that students become more active in participating in learning activities. Before using Kahoot, the learning process mostly used the lecture method, which made students less enthusiastic. After Kahoot was implemented, students became more focused and interested in answering the quiz questions. In addition, Kahoot also helps teachers deliver learning materials and conduct evaluations more easily. Overall, the use of Kahoot has a positive impact on increasing student engagement in mathematics learning at the elementary school level.